Retinotoxicity of Hydroxychloroquine: Is It Possible to Demonstrate by Spectral Domain Optical Coherence Tomography Before Development? A Cross Sectional Investigation - Hasan Fatih ÇAY,; Muhammet Kazım EROL,; Deniz TURGUT ÇOBAN,; Mehmet BULUT,; İlhan SEZER,; Tuncay ÇAKIR,; Naciye Füsun TORAMAN, (Archives of Rheumatology, 2014)
Objectives: This study aims to evaluate the alterations of retinal layers in rheumatic patients treated with hydroxychloroquine but without the signs or symptoms of retinopathy by using spectral domain ocular coherence tomography (SD-OCT). Patients and methods: The retinal layers of a total of 402 eyes including 114 patients treated with hydroxychloroquine (for rheumatoid arthritis (n=40), Sjögren’s syndrome (n=47) and connective tissue diseases (n=27) and age-matched 87 healthy controls were evaluated with SD-OCT. The macular cube protocol, optic disc cube protocol and horizontal and vertical HD 5-line raster scan protocol were applied. The measured parameters were compared between hydroxychloroquine users and healthy control group. The results of these parameters were also compared with other disease groups using hydroxychloroquine. The correlation of these parameters with the duration of drug consumption and dose was assessed. Results: All layers of outer fovea, superior and inferior quadrants of retinal nerve fiber layers of hydroxychloroquine users were thinner than non-users. Connective tissue disease group had longer duration and higher cumulative dose of hydroxychloroquine than other diagnostic groups. This group had thinner mean retinal nerve fiber layers values than the other groups as well. There were significant and negative correlations between cumulative dose of drug and parafoveal region thickness of outer fovea and inferior quadrant of retinal nerve fiber layers. Thickness of parafoveal and perifoveal layers was negatively correlated with the dose of drug per kg of body weight. Conclusion: Our study results show that SD-OCT may be the golden standard technique for the follow-up of antimalarial-induced retinotoxicity in future.